End Semester Student Endurance in Completing Thesis at Muhammadiyah University of Sidoarjo for Academic Year 2020-2021 - Mohammad Rizalluddin Akbar; Ririn Dewanti Dian (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study is to find out how hardiness is described in final semester students in completing thesis at Muhammadiyah University of Sidoarjo in the academic year 2020-2021 and what factors affect hardiness in final semester students in completing thesis at Muhammadiyah University Sidoarjo in the academic year 2020-2021 quantitatively. descriptive. The population in this study were 1152 students in the final semester of Muhammadiyah University of Sidoarjo with a sample of 293 people based on Krejcie and Morgan tables. The data collection technique in this study uses a psychological scale, namely the hardiness scale in the form of a Likert scale. The results of the validity test were obtained as many as 24 valid items from the 26 items compiled. The result of the reliability test is 0.930. With the results of the study showing that the hardiness of final semester students in completing their thesis at the University of Muhammadiyah Sidoarjo in 2021, almost half (48.1%) have hardiness in the medium category, less than half and get a percentage of 48.1%, a small proportion have low hardiness. (28.3%), but a small proportion still have high hardiness (23.5%). Based on gender, female students have more hardiness (50.6%) than male students (44.4%). Factors that affect hardiness more are social support (59%) than parenting (41%).